Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 11 - Rational Expressions and Functions - 11-5 Solving Rational Equations - Practice and Problem-Solving Exercises - Page 684: 35



Work Step by Step

Given:$\dfrac{3}{s-1}-\dfrac{12}{s^2-1}=-1$ Need to find least common denominator(LCD). $\dfrac{3(s+1)-12}{s^2-1}=-1$ $\dfrac{3s+3-12}{s^2-1}=-1$ $\dfrac{3s-9}{s^2-1}=-1$ Apply cross products. $3s-9=-1(s^2-1)$ $3s-9=-s^2+1$ $-s^2+1-3s+9=0$ or, $(s-2)(s+5)=0$ Hence, $s=2,-5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.